Distribution of Escerichia coli serotype OIKi, 02Kt, and O7sK8o in poultry in Indonesia - Poernomo, Sri; Juarini, E. (Indonesian Animal Sciences Society, 1995)
Fowl colibacillosis or colisepticaemia is commonly caused by Eschercia coli serotypes OIKI, 02Kt, and O7sKgo . To understand the distribution of these three serotypes of E. coli in poultry breeding farms in Indonesia, samples were collected from surveyed areas of Jakarta, Bogor, Tengerang, Bekasi and Sukabumi, West Java, Central Java, East Java, Bali, North Sumatera, Lampung, West Kalimantan and South Sulawesi . A total of 2,454 samples which consisted of 1,413 organs of sick birds, 398 feed, 336 drinking water and 307 litter, were collected throughout the surveyed areas . The specimens were then examined bacteriologically toward the presence of E. coli . As many as 950 E. coli isolates consisting of 85 (9 .0%) OIKI ; 489 (51 .5%) 02KI ; 101 (10.6%) 078K8o, and 275 (28.9%) of other serotypes were isolated from the samples . Key word : Escherichia coli, colibacillosis, chicken